About/of madness: Ann Quin's The Unmapped Country. Issue 6 (2nd June 2020) - Williams, Nonia
ABSTRACT: Ann Quin's final, unfinished book, The Unmapped Country (1973), narrates its protagonist's experience of madness. This article considers Quin's text in light of Shoshana Felman's distinction in Writing and Madness (1978), between writing 'about' madness, at a distance from the experience, and writing 'of' it: how, Felman asks of the latter, might this even be possible? The distinction between about and of, and the question of how? structure my argument here. I propose that Quin's method of reiteration is particularly significant, because it shifts focus away from what madness is, to ask what it does; what madness does to language, and how this is caught up with questions of institutionalisation. It is precisely the strange overload and cliché of the writing, I argue, which enables it to enact a madness that always necessarily eludes direct narrative expression. Because this effect arises from proliferation at word level, rather than providing a broader historical or social discussion of notions of madness in Quin's era, I track and attend closely to the formal mechanisms and language of The Unmapped Country, and in particular to the effect of the layers and echoes of its influences and intertexts – from George Eliot to Virginia Woolf.